2020
DOI: 10.1016/j.jaac.2019.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Translating Discoveries in Attention-Deficit/Hyperactivity Disorder Genomics to an Outpatient Child and Adolescent Psychiatric Cohort

Abstract: Objective Genomic discoveries should be investigated in generalizable child psychiatric samples in order to justify and inform studies that will evaluate their use for specific clinical purposes. In youth consecutively referred for neuropsychiatric evaluation, we examined 1) the convergent and discriminant validity of attention-deficit/hyperactivity disorder (ADHD) polygenic risk scores (PRSs) in relation to DSM -based ADHD phenotypes; 2) the association of ADHD PRSs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…These findings are similar to a study of a clinical ADHD population that found a larger difference in levels of hyperactivity symptoms than inattention symptoms between high and low PRS groups. 11 One explanation for this could be that genetic risk identified by the PRS derived from the current ADHD GWAS is more related to hyperactivity/impulsivity symptoms than inattention symptoms. Children exhibiting externalizing-type problems are more likely to come to clinical attention, leading to a higher likelihood of these children being included in pediatric clinical populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings are similar to a study of a clinical ADHD population that found a larger difference in levels of hyperactivity symptoms than inattention symptoms between high and low PRS groups. 11 One explanation for this could be that genetic risk identified by the PRS derived from the current ADHD GWAS is more related to hyperactivity/impulsivity symptoms than inattention symptoms. Children exhibiting externalizing-type problems are more likely to come to clinical attention, leading to a higher likelihood of these children being included in pediatric clinical populations.…”
Section: Discussionmentioning
confidence: 99%
“…That a relatively small amount of variance in symptoms is explained by the PRS has been found in other studies; for example, a recent study in a clinical ADHD cohort found the PRS explained 1.8%–2.9% of variance in ADHD symptom level. 11 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, ADHD-PRS was found to associate with symptoms of hyperactivity-impulsivity and to be mediated by white matter microstructure in brain regions that have been suggested to have a role in ADHD pathology 51,52 . In addition, ADHD-PRS was found to predict educational achievement 53 , to be linked with the severity of the clinical profile in those with high PRS 54 , and even to predict MPH response 55 . Although the etiology and pathways involved in ADHD cannot be revealed by using PRS only, this approach seems to be a powerful tool studying endophenotypes of the heterogeneous disorder.…”
Section: Genetic Evidence For Wnt-signaling In Adhdmentioning
confidence: 98%